Winter conditions, not resource availability alone, may drive reversible seasonal skull size changes in moles - Nováková, Lucie; Lázaro, Javier; Muturi, Marion; Dullin, Christian; Dechmann, Dina K. N. (Royal Society Open Science, 2022)
Seasonal changes in the environment can lead to astonishing adaptations. A few small mammals with exceptionally high metabolisms have evolved a particularly extreme strategy: they shrink before winter and regrow in spring, including changes of greater than 20% in skull and brain size. Whether this process is an adaptation to seasonal climates, resource availability or both remains unclear. We show that European moles (Talpa europaea) also decrease skull size in winter. As resources for closely related Iberian moles (Talpa occidentalis) are lowest in summer, we predicted they should shift the timing of size changes. Instead, they do not change size at all. We conclude that in moles, seasonal decrease and regrowth of skull size is an adaptation to winter climate and not to a changing resource landscape alone. We not only describe this phenomenon in yet another taxon, but take an important step towards a better understanding of this enigmatic cycle.
Gesehen am 23.01.2023